2019
DOI: 10.4102/sajhivmed.v20i1.847
|View full text |Cite
|
Sign up to set email alerts
|

HIV viraemia during pregnancy in women receiving preconception antiretroviral therapy in KwaDukuza, KwaZulu-Natal

Abstract: Background: Preconception antiretroviral therapy (PCART) followed by sustained viral suppression is effective in preventing mother-to-child transmission of HIV. The rates of persistent and transient viraemia in such patients have not been prospectively assessed in South Africa.Objectives: We determined the prevalence of transient and persistent viraemia in HIV-positive women entering antenatal care on PCART and studied variables associated with viraemia.Methods: We performed a prospective cross-sectional obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 48 publications
2
11
0
Order By: Relevance
“…There was, however, no significant correlation between HIV status and antibiotic use or treatment duration (p = 0.9). This might indicate the positive impact of antiretroviral (ARV) therapy on decreasing the Similarly, these results were found in KwaZulu-Natal and Nigeria, although this explanation cannot be extrapolated to the general population and is limited to this study (Calder et al 2020;Mepham et al 2011;Ntlantsana et al 2019).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…There was, however, no significant correlation between HIV status and antibiotic use or treatment duration (p = 0.9). This might indicate the positive impact of antiretroviral (ARV) therapy on decreasing the Similarly, these results were found in KwaZulu-Natal and Nigeria, although this explanation cannot be extrapolated to the general population and is limited to this study (Calder et al 2020;Mepham et al 2011;Ntlantsana et al 2019).…”
Section: Discussionmentioning
confidence: 56%
“…The prevalence of the HIV in South Africa remains high (Cohn & Clark 2014;Ntlantsana, Hift & Mphatswe 2019) and considering the large percentage of HIV-positive women in this study, it was expected that the duration of antibiotic therapy and the number of prescriptions dispensed to these women would be higher compared with HIV-negative pregnant women. There was, however, no significant correlation between HIV status and antibiotic use or treatment duration (p = 0.9).…”
Section: Discussionmentioning
confidence: 90%
“…One third of our study's participants had detectable viral load which is higher than that documented in other studies using the same cutoff of 50 copies/ml. Studies from South Africa 11,14,17 and Malawi 18 documented lower prevalence of detectable viral load among HIV infected pregnant women ranging from 10% to 23%. Much as various studies have demonstrated the association between detectable viral load and poor or non-adherence to ART, 7,[19][20][21][22] we cannot speculate non-adherence as a plausible explanation for the high prevalence of undetectable viral load since we did not measured non-adherence at this point in time.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, close to 35 million people are believed to live with HIV. Sub-Saharan Africa, worst affected region, in particular accounts for 71% of HIV infections [1]. Life expectancy for patients infected with HIV has improved significantly in the era of highly active antiretroviral therapy (HAART) [2].…”
Section: Introductionmentioning
confidence: 99%